Induction of delayed-type hypersensitivity in human volunteers immunized with a candidate leprosy vaccine consisting of killed Mycobacterium leprae - Gill, H. K. (1986)
A killed armadillo-derived Mycobacterium leprae vaccine was examined for its ability to induce a delayed-type hypersensitivity (DTH) response in purified protein derivative (PPD)-positive human volunteers living in a leprosy non-endemic country. Four groups of individuals aged between 23 and 28 years were given 1.5 × 10(7), 5 × 10(7), 1.5 × 10(8) and 5 × 10(8) M. leprae intradermally. A marked increase in reactivity to the M. leprae-derived skin test antigen (MLSA) was observed in the vaccinated groups receiving the three highest doses of vaccine while there was very little change observed in their PPD reactivity. No unacceptable side-effects attributable to the vaccine were observed. The killed armadillo-derived M. leprae vaccine thus appears to be able to induce a DTH response in man at doses which do not cause unacceptable side-effects.